In-hospital prognosis in patients with myocardial infarction and atrial fibrillation. (26th April 2021) - Leonova, I; Solovyeva, M; Boldueva, S; Bykova, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The number of patients with myocardial infarction (MI) and atrial fibrillation (AF) is increasing every year. Purpose: to assess the incidence of AF among the patients with MI, the features of the in-hospital prognosis among the patients with MI and AF compared with MI without AF. Methods: The patients with type 1 MI and preexisting AF have been selected from all MI patients MI admitted in 2013-18. They have formed the main group (100 patients). The control group (200 patients with type 1 MI without AF), has been created by "pair selection" method. Patients in the groups did not differ in gender, age, MI date and had not severe comorbidities. Results: 1660 patients with MI were analyzed. AF occurred in 309 patients (18.6% of patients with MI). Preexisting AF was in 59.2%. Patients with MI and AF were older than MI without AF (mean age 75.2 ± 10.1 versus 64.6 ± 12.8, p <0.0001) with women's prevalence (52.4% versus 35.5%, p <0.0001). Type 1 MI predominates among all patients. Type 2 MI occurred 5 times more often among main group (p <0.0001). 2 groups were adjusted for sex (58% of women in both groups), age (mean age 75.5 ± 8, 7 in the main versus 75.2 ± 8.5 in the control group, p = 0.775). Diabetes (45% versus 31.5%, p = 0.030), previous MI (40% versus 25.5%, p = 0.012) and stroke (21% versus 11.5%, p = 0.037) were more common in the main than in the control. Patients with MI and AF had lower GFR (56.8 ± 19.4 versus 61.7 ± 17.9 ml/min/1.73 m2, p = 0.031), LDL (2.8 ± 0.9 versus 3.3 ± 1.0 mmol/L, p = 0.0002). Patients with AF had a lower left ventricular ejection fraction (55.2 ± 10.5 versus 59.8 ± 10.0 %, p = 0.0005). Significant mitral regurgitation was more common in the main group (53.9% versus 30.3% in the control group, p = 0.0002). There were no differences in the incidence of acute heart failure (HF) Killip's 3-4 (20% versus 13%, p = 0.127). Patients did not differ in the number of affected coronary artery (p = 0.7327), the level of stenosis (p = 0.1956), in the frequency of revascularization (p = 0.0686). Patients with MI and AF had worse in-hospital prognosis. Pulmonary embolism (PE) (9% in main versus 1% in control group, p = 0.0011), minor bleeding (21% versus 9.5%, p = 0.0057), combined endpoint (stroke + PE + mortality) (19% versus 10.5%, p = 0.0415) were more common in the main group. At discharge, patients with AF had HF III NYHA in 21.8% cases versus 5.5% in patients without AF, p = 0.0001. There were no significant differences in other in-hospital endpoints (recurrent myocardial infarction, stroke, major bleeding, and mortality) between the groups. In-hospital mortality was 13% in the main versus 9.5% in the control group (p = 0.4276). Conclusion: AF occurs in 18.6% of patients with MI. Patients with AF and MI are older with female prevalence. Type 1 MI predominates. Patients with type 1 MI and pre-existing AF is a group of high risk because of more severe HF, PE, minor bleeding and combined endpoint (stroke + PE + mortality)